Shelf life Extension of Tuna Fillets by Gelatin and Chitosan Based Edible Coating Incorporated with Clove Oil - Kumar, K. Sathish; Chrisolite, B.; Sugumar, G.; Bindu, J.; Venkateshwarlu, G. (Fishery Technology, 2018)
The present study aimed to develop bioactive edible coating (BEC) solutions from gelatin and chitosan, incorporated with different concentrations of clove oil as a natural preservative and evaluate their effect on shelf life of tuna fillets. The antibacterial activity against 11 fish spoilage and fish-borne bacteria were tested by agar well diffusion method, minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). Gram positive bacteria were more susceptible than gram negative bacteria. Among all the tested bacteria, Bacillus cereus and Staphylococcus aureus were most sensitive to BEC solutions. The tuna fillets were dipped in BEC solutions with different concentrations viz., 1% Acetic acid, 1% Chitosan (C), 1% Gelatin + 1% Clove oil (GC), 1% Chitosan + 1% Clove oil (CC), 1% Gelatin + 1% Chitosan + 1% Clove oil (GCC) and changes in APC, TBARS, TVB-N and sensory values were studied during storage under refrigerated condition (4Â°C). The fillets without dip treatment was considered as control. Dip treatment of BEC solutions significantly delayed the rate of microbial spoilage and extended the shelf life of tuna fillets by six days during refrigerated storage. Solutions incorporated with clove oil, especially fillets treated with 1% gelatin + 1% chitosan + 1% clove oil (GCC) solution had better in-vitro antimicrobial properties and showed excellent preservative action on tuna fillets. The BEC solutions incorporated with clove oil demonstrated its potential as an excellent natural antibacterial agent which can be used as an effective alternative to synthetic antibacterial agents and could be used for packaging of tuna and other fishery products.